Drought risk and vulnerability in water supply systems - Cubillo F.; Garrote L. (Drought management: scientific and technological innovations, 2008)
This paper provides an overview of the challenges presented to the managers of water supply systems by drought and water scarcity. Risk assessment is an essential tool for the diagnostic of water scarcity in this type of systems. The evaluation of the risk of water shortage is performed with the use of complex mathematical models. Different alternatives to address the problem are presented, covering a range of methodological approaches. The actions adopted to prevent or mitigate the effects of water scarcity should be properly organized in drought management plans. The process of development and implementation of drought management plans is briefly described presenting several examples taken from the Mediterranean region.
1. International Conference Drought Management: Scientific and Technological Innovations, 2008/06/12-14, Zaragoza (Spain)